Analysis of the Implementation of Project-Based Learning Method During the Pandemic Covid-19 - Siska Siska; Tri Indah Rusli; Nur Rizky Alfiani Syuaib (FKIP Universitas Muhammadiyah Kendari, 2022)
This study was conducted to describe the teacher’s process of teaching English by implementing project-based learning method during the pandemic covid-19 by using Whatsapp. This study use qualitative design and the data collection techniques used observation sheet, and interview. The data analysis uses Miles Huberman and Saldana concept and the participant of this study only one teacher who teaches in the 7th grade at SMPS Kartika XX-6 Kendari. The results showed that based on the project-based learning steps in the 2013 curriculum, the teacher only applies 4 steps such as: 1) creating a set schedule means the teacher determines the time when student projects must be collected. 2) monitoring student projects because learning is done online, so teachers involve parents in monitoring students during the learning process and completing projects, 3) assessing student's outcomes, the teacher assigns a value to the student project according to the scoring rubric created, 4) evaluating students' experiences, the teacher provides feedback to students so they can correct the mistakes they made. The teacher gives a project in the form of a video regarding conversations about greetings, self-introductions and talking about daily activities with the aim that students get used to speaking in English. Project work is carried out individually by students due to the online learning process as a result of the covid-19 pandemic which was submitted by using WhatsApp.